MODERN METHODS OF TEACHING NETWORK TECHNOLOGIES - Begbo'tayev, Azam (Журнал математики и информатики, 2021)
Abstract: The article analyzes research on the problem of shaping individual education using SMART -technologies in higher education the in conditions COVUD-19. The purpose of the article - methodological recommendations for creating an integrated learning environment in educational institutions using SMART-technologies and the Internet of Things (IoT) in the university teaching the subject "Network Technologies", the basic principles of their work and the main features are formed. As research methods, the author used interpretation, comparative analysis, and generalization of the scientific literature on the problem; The example of SMART-technology tools and IoT-Internet of Things tools analyzes the relevance and validity of their use from a didactic point of view, emphasizing the need to constantly improve the learning process with their help.